Resúmenes de novedades - Foro Internacional, Revista (Foro Internacional, 2023)
John J. Mearsheimer y Sebastian Rosato, How States Think: The Rationality of Foreign Policy, New Haven, Yale University Press, 2023, 304 pp. Dominique Colas, Poutine, l’Ukraine et les statues de Lénine, París, Presses de Sciences Po, 2023, 144 pp. Steven Levitsky y Daniel Ziblatt, Tyranny of the Minority: Why American Democracy Reached the Breaking Point, New York, Crown, 2023, 384 pp. Mark Sedgwick, Traditionalism: The Radical Project for Restoring Sacred Order, Nueva York, Oxford University Press, 2023, 384 pp. Zongyuan Zoe Liu, Sovereign Funds: How the Communist Party of China Finances Its Global Ambitions, Massachusetts, Belknap Press, 2023, 288 pp. Larry M. Bartels, Democracy Erodes from the Top: Leaders, Citizens, and the Challenge of Populism in Europe, Princeton, New Jersey, Princeton University Press, 2023, 280 pp. Paul Gowder, The Networked Leviathan: For Democratic Platforms, Cambridge, Reino Unido, Cambridge University Press, 2023, 255 pp. Peter A. Hall, Georgina Evans y Sung In Kim, Political Change and Electoral Coalitions in Western Democracies, Cambridge, Reino Unido, Cambridge University Press, 2023, 90 pp. Samuel Moyn, Liberalism against Itself: Cold War Intellectuals and the Making of Our Times, New Haven, Yale University Press, 2023, 240 pp. Astrid von Busekist, La Religion au tribunal: Essai sur le délibéralisme, París, Albin Michel, 2023, 384 pp.